Retrospective evaluation of the clinical use of prothrombin complex concentrate for the reversal of anticoagulation with vitamin K antagonists. Issue 4 (June 2015) - Cruz, Jennifer L.; Moss, Mary C.; Chen, Sheh-Li; Hansen, Kayla M.; Amerine, Lindsey B.
Abstract : Anticoagulation reversal is a time-sensitive intervention for the prevention of life-threatening hemorrhagic events occurring with bleeding or surgery. Recommendations for the most effective and well tolerated reversal agent in these settings remain controversial. Several clinical guidelines for the management of intracerebral hemorrhage support use of prothrombin complex concentrates (PCCs) for the rapid reversal of warfarin-associated coagulopathy despite limited clinical data. The purpose of this investigation was to evaluate the efficacy and safety of PCC for the rapid reversal of anticoagulation by vitamin K antagonists for life-threatening bleeding or emergent surgery and to assess adherence to a hospital-based protocol. A retrospective chart review was conducted of adult patients receiving PCC for the reversal of anticoagulation. Patients were assessed according to indication for anticoagulation reversal. The primary outcome measure was adequacy of international normalized ratio reversal. Other outcomes included cessation of bleeding, thrombotic complications, and adherence to an institutional-based guideline for the use of PCC. ICU and hospital length of stay and 30-day mortality was assessed. There were 70 patients included in this study. Mean international normalized ratio was reduced from 3.1 to 1.6 following administration of at least one dose of PCC. Cessation of bleeding occurred in 65.7% of patients. Clinical assessment was unclear in 18.6%. Thrombotic complications were observed in 7.1% of patients. The 30-day mortality rate was found to be 14.3%. These data demonstrate that PCC is a well tolerated and effective method for anticoagulation reversal associated with a relatively high 30-day survival rate.